Attentional entrainment and perceived event duration - McAuley, J. Devin (Philos Trans R Soc Lond B Biol Sci, 2014)
This study considered the contribution of dynamic attending theory (DAT) and attentional entrainment to systematic distortions in perceived event duration. Three experiments were conducted using an auditory oddball paradigm, in which listeners judged the duration of a deviant (oddball) stimulus embedded within a series of identical (standard) stimuli. To test for a role of attentional entrainment in perceived oddball duration, oddballs were presented at either temporally expected (on time) or unexpectedly early or late time points relative to extrapolation of the context rhythm. Consistent with involvement of attentional entrainment in perceived duration, duration judgements about the oddball were least distorted when the oddball occurred on time with respect to the entrained rhythm, whereas durations of early and late oddballs were perceived to be shorter and longer, respectively. This pattern of results was independent of the absolute time interval preceding the oddball. Moreover, as expected, an irregularly timed sequence context weakened observed differences between oddballs with on-time and late onsets. Combined with other recent work on the role of temporal preparation in duration distortions, the present findings allot at least a portion of the oddball effect to increased attention to events that are more expected, rather than on their unexpected nature per se.